Exploring the Influence of Transformational Leadership Style and Motivation on Employee Performance - Dayanti, Agustina; Nurchayati, Nurchayati (Research Horizon, 2023)
This research aims to explore the impact of the transformational leadership style and motivation on employee performance, while considering job satisfaction as an intervening variable. The research population comprises all employees of the Department of Public Works and Spatial Planning in Batang Regency, totaling 133 individuals, with a sample size of 100 respondents. The Proportional Simple Random Sampling technique was employed for sampling, utilizing a lottery method. The data analysis technique used in this study was path analysis. The research findings indicate that both the transformational leadership style and motivation have a positive and significant influence on employee performance, as well as a positive and significant impact on job satisfaction. Specifically, the transformational leadership style indirectly affects employee performance through its influence on job satisfaction. However, it is noted that motivation does not significantly influence employee performance through job satisfaction. This suggests that strategies for motivational development need to be tailored and integrated with internal and external factors that can more directly affect employee performance. These factors could include improvements to the work environment, incentive structures, career prospects, and other relevant aspects.